2023
DOI: 10.1037/xlm0001212
|View full text |Cite
|
Sign up to set email alerts
|

Are goats chèvres, chévres, chēvres, and chevres? Unveiling the orthographic code of diacritical vowels.

Abstract: An often overlooked but fundamental issue for any comprehensive model of visual-word recognition is the representation of diacritical vowels: Do diacritical and nondiacritical vowels share their abstract letter representations? Recent research suggests that the answer is “yes” in languages where diacritics indicate suprasegmental information (e.g., lexical stress, as in [‘ka.ma.ɾa] camera; Spanish), but “no” in languages where diacritics indicate segmental information such as a different phoneme (e.g., the Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Only a few studies have recently investigated whether there is a cost associated with the addition of non-existent diacritics to words. Labusch et al (2023) conducted a semantic categorization task on non-diacritical French words [e.g., chēval vs. cheval (horse); the macron diacritic in ē does not exist in French] and found a small advantage of intact words (around 11 ms) over those with an additional non-existent diacritic. Furthermore, in a masked priming lexical decision experiment in English, Perea et al (2023a) found that the recognition of a target word such as CLOCK was 7 ms faster when the identity prime was intact (e.g., clock) than when the identity prime had an additional diacritic (e.g., clóck).…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies have recently investigated whether there is a cost associated with the addition of non-existent diacritics to words. Labusch et al (2023) conducted a semantic categorization task on non-diacritical French words [e.g., chēval vs. cheval (horse); the macron diacritic in ē does not exist in French] and found a small advantage of intact words (around 11 ms) over those with an additional non-existent diacritic. Furthermore, in a masked priming lexical decision experiment in English, Perea et al (2023a) found that the recognition of a target word such as CLOCK was 7 ms faster when the identity prime was intact (e.g., clock) than when the identity prime had an additional diacritic (e.g., clóck).…”
Section: Introductionmentioning
confidence: 99%
“…For languages using the Roman script (for instance, English, Spanish, and French, among others), it may be difficult to isolate phonological and orthographical effects due to strong grapheme-phoneme correspondences (the strong overlap between orthography and phonology) ( Vasilev et al, 2019 ; Meade, 2020 ). Recent studies have also shown that the grapheme-phoneme pattern regulates the effect of phonology on the time course of word processing ( Labusch et al, 2022 ). Moreover, even orthographic control condition typically shares one phoneme (at least) of the target word.…”
Section: Introductionmentioning
confidence: 99%